2005
DOI: 10.1373/clinchem.2004.045120
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin and other Adipocytokines as Predictors of Markers of Triglyceride-Rich Lipoprotein Metabolism

Abstract: Visceral and subcutaneous adipose tissue masses (ATMs) were determined by magnetic resonance imaging and total ATM by bioelectrical impedance. Results: In univariate regression, plasma adiponectin and leptin concentrations were inversely and directly associated with plasma apoB-48, apoC-III, RLP-cholesterol, triglycerides, VLDL-apoB, and VLDL-triglycerides (P <0.05). Resistin, IL-6, and TNF-␣ were not significantly associated with any of these variables, except for a direct correction between apoC-III and IL-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
59
1
4

Year Published

2006
2006
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 44 publications
12
59
1
4
Order By: Relevance
“…This hypothesis is consistent with our finding that adiponectin correlated with the FCR of VLDL 1 TG and ApoB and the FTR of VLDL 1 TG, and is consistent with recent data by Ng et al [52]. Notably, adiponectin stimulates (via its action on PPARα) the expression of Apo-CIII, which regulates the metabolism of TGs [53].…”
Section: Discussionsupporting
confidence: 94%
“…This hypothesis is consistent with our finding that adiponectin correlated with the FCR of VLDL 1 TG and ApoB and the FTR of VLDL 1 TG, and is consistent with recent data by Ng et al [52]. Notably, adiponectin stimulates (via its action on PPARα) the expression of Apo-CIII, which regulates the metabolism of TGs [53].…”
Section: Discussionsupporting
confidence: 94%
“…A high correlation coefficient between leptin and TG values after exercise (r 5 0.65) was found. Similar results were reported in the study of non-diabetic humans, in which the plasma leptin concentration was directly and highly associated with plasma TG level (Chan et al, 2005).…”
Section: Discussionsupporting
confidence: 89%
“…increased fasting triglycerides and low HDL cholesterol), as it relates to type 2 diabetes and the IRS [47,48]. It has been suggested that adiponectin concentration may play an independent role in regulating TRL metabolism, aside from its link with abdominal fat, insulin resistance and dyslipidaemia [47]. These observations have relevance to a recent finding where a significant correlation was demonstrated between the expression of ADIPOR1 and ADIPOR2 mRNA in human skeletal muscle and in vivo parameters of glucose and lipid metabolism [49].…”
Section: Discussionmentioning
confidence: 90%
“…There has been considerable interest in the role of kinetic defects in triglyceride-rich lipoprotein (TRL) metabolism in the development of atherosclerosis and dyslipidaemia (e.g. increased fasting triglycerides and low HDL cholesterol), as it relates to type 2 diabetes and the IRS [47,48]. It has been suggested that adiponectin concentration may play an independent role in regulating TRL metabolism, aside from its link with abdominal fat, insulin resistance and dyslipidaemia [47].…”
Section: Discussionmentioning
confidence: 99%